Magnetic investigation of an unusual dissymmetric binuclear manganese carboxylate complex [Articol] - Novitchi, Ghenadie; Costes, Jean-Pierre; Popovschi, Lilia; Shova, Sergiu; Gulea, Aurelian (Institute of Chemistry of ASM, 2006)
The magnetic susceptibility (χT) of an unusual dissymmetric binuclear manganese corboxylate complex has been measured from 2 to 300K. The magnetic data which have been fitted with help of the Heisenberg Dirac Van Vleck HDVV spin-exchange Hamiltonian HJSS=−urur, indicate that an antiferromagnetic interaction equalto J = 0.90(1) cm-1 ispresent. A correlation between J values andMn-H2O-Mn angles has been tempted.
Keywords: manganese(II) carboxylates; magnetic properties